Peningkatan Kualitas Hidup Penderita Kusta Dengan Menggunakan Metode Self Help Group (SHG) - Ifa Roifah (Akademi Keperawatan Dharma Husada Kediri, 2017)
Leprosy is one of the infectious diseases that cause a very complex problem, not only from a medical point of view. In addition there is a negative stigma from the community tends to cause the quality of life of people with leprosy decline. Quality of life is the concept of individual ability analysis to get a normal life associated with individual perceptions of goals and expectations, one of the measures to improve the quality of life of leprosy is by doing Self Help Group (SHG) therapy. This study aims to determine the quality of life in people with leprosy. The design of this research using pra experiment with pretest-posttest design approach. The samples were taken with the techniques of cluster random sampling as much as 15 respondents. Tool used WHOQOL-BREF questionnaire containing 26 questions. Patients with leprosy prior to being given Self Help Group (SHG) from 15 respondents mostly experience poor quality of life 7 people (46,7%), leprosy patient after given Self Help Group (SHG) that from 15 respondents mostly experience quality of life is 5 people (33.3%). The test used is using Wilcoxon Signed Rank Test. p value = 0,007 and α = 0,05 so Ha is accepted, it means there is influence Self Help Group therapy (SHG) to quality of life in leprosy patients in tanjungkenongo village sumberglagah kec. Pacet kab. Mojokerto. Self Help Group (SHG) is a group or peer where each member share the same physical or emotional issues or specific issues where they work together to share problems and choose what will be the focus of solving group members, helping each other in motivating to create a sense of prosperity.